2014
DOI: 10.5539/ijbm.v9n8p122
|View full text |Cite
|
Sign up to set email alerts
|

How Social Network Characteristics Affect Users’ Trust and Purchase Intention

Abstract: These days, young college students cannot imagine life without social network service (SNS). They access and browse social network sites everyday to get information, find friends, enjoy entertainment, and express their opinion. Despite an extraordinary amount of time consumed on SNS by young adults, there have not been extensive researches and discussion of social networking services and their impact on purchase intention. The aim of this research is to discover how SNS characteristics affect SNS users' trust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
1
16
0
3
Order By: Relevance
“…Accordingly, consumers place excellent value on eWOM opinions from close contacts, family, and key opinion leaders from electronic media. Therefore, marketers target and segment customers more efficiently within these platforms, including the understanding of customers' attitudes [4,57]. Organizations and individuals have adopted social media usage [58], and have altered the discussion's nature, facilitating trades to connect with customers and build intense and increased sales [1,59].…”
Section: Moderating Role Of Social Media Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, consumers place excellent value on eWOM opinions from close contacts, family, and key opinion leaders from electronic media. Therefore, marketers target and segment customers more efficiently within these platforms, including the understanding of customers' attitudes [4,57]. Organizations and individuals have adopted social media usage [58], and have altered the discussion's nature, facilitating trades to connect with customers and build intense and increased sales [1,59].…”
Section: Moderating Role Of Social Media Usagementioning
confidence: 99%
“…Social media has rapidly become one of the world's leading platforms for distributing information between marketers and consumers worldwide [1,2]. With the fast development of social networking sites, smartphone acceptance, internet speed, and wireless network coverage, social media users can now interact with their friends and accelerate the exchange and retrieval of information via their mobile phones and tablets [3,4]. According to the statistical data reported by the end of December 2018, nearly 98% of people in China have access to the Internet via smartphones and other social networking sites; out of those, 48% of people purchase online fashion products [5].…”
Section: Introductionmentioning
confidence: 99%
“…This information generated on social commerce websites increases trust (Hajli et al, 2014). It has been shown that information provided by users on websites positively affects trust (Filieri, 2015;Han, 2014;Kuan and Bock, 2007;Bock et al, 2012). Because Z-ers and Y-ers seem to be most active on the Internet, since they are used to online environments, it is assumed that they will tend more toward user-generated information.…”
Section: Development Of Hypotheses and Research Modelmentioning
confidence: 99%
“…On the one hand, in social commerce contexts, trust is increased by social WOM – that is, the information shared by users. Indeed, several authors have stated that user-generated information has a positive effect on trust (Filieri, 2015; Han, 2014; Kuan and Bock, 2007; Bock et al , 2012). On the other, users can develop trust based on website content provided by the company (Chen et al , 2015; Beldad et al , 2010; Kim and Park, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the challenges of online SNSs sellers as opposed to established and well-known firms is to gain trust and reputation from customers to participate in the selling and buying activities. Studies have investigated the factors that influence customers' purchase intention from various dimensions and theories (Han, 2014;Hajli, 2015;Che and Cheung, 2017;Hsu et al, 2017;Pothong and Sathitwiriyawong, 2017;Chen, Hsiao, and Wu, 2018). However, there is still insufficient research specifically study on the customers' purchase intention in social commerce (Esmaeili and Hashemi G., 2019).…”
Section: Introductionmentioning
confidence: 99%